Factors influencing consumers’ purchasing behaviour of pharmaceuticals in South Africa - Chihururu, Constance (University of the Witwatersrand, Johannesburg, 2023)
Purpose: This study aims to identify the intrinsic and extrinsic factors influencing purchasing decisions for pharmaceuticals among South African consumers. Methodology: A descriptive quantitative approach was employed, utilizing an online questionnaire distributed through nonprobability snowball sampling. The sample consisted of 246 South African consumers aged 18 and above who had recently purchased pharmaceuticals. Findings/Results: Using regression analysis, Price, product information, and patient experience were found to significantly impact consumer purchase intention and actual purchase. Consumer trust in the product improved price tolerance and influenced actual purchases. Practical implications: The findings have practical implications for pharmaceutical companies, marketers, policymakers, and healthcare providers. Tailoring marketing strategies, optimizing packaging designs, and providing comprehensive product information can enhance consumer purchase intentions and stimulate actual purchases. Policymakers and healthcare providers can optimize resource allocation, cost- effectiveness, and reduce unnecessary healthcare expenditures by targeting interventions that enhance consumer knowledge, promote competitive pricing, and ensure transparent product information. Originality/value: This study contributes to the existing body of knowledge on factors influencing the purchasing behaviour of South African consumers towards pharmaceuticals. It fills a research gap by providing specific insights into consumer behaviour in this context, offering practical implications for decision-makers and adding to the literature on consumer behaviour studies in South Africa
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Consumer purchase behaviour; Pharmaceutical products; South Africa; Purchase decision; UCTD; SDG-8: Decent work and economic growth